Brooklyn Central - Roy, Debjit; Nayak, Sonali (London : Indian Institute of Management, Ahmedabad, 2020)
Keeping in mind the need, lifestyle, and tastes of Indian diners, Brooklyn Central had brought a change in taste and experience by introducing an American-style restaurant in Chandigarh, India. Factors like location, customers, layout, menu, pricing, theme, organization structure, and advertisement, which have important roles in the success of the business, are discussed in the case. This case can be used to look at best practices in restaurant management.The case throws up a number of questions. In spite of its prices being higher than other cafes, why were the footfalls high at Brooklyn Central? Why would a customer be willing to pay a higher price for a burger at Brooklyn Central than for a happy meal at MacDonald's or Burger king? What kind of customers did the restaurant target? What strategies did it use to retain customers and get them to spend more for an item like a burger? How challenging is it for a popular restaurant to maintain consistency in its food and service? How difficult was it for Brooklyn Central to change its menu? What methods did it adopt to minimize food wastage? How did it manage the weekend crowd with limited seating?
Description based on XML content.
Keywords: elektronické knihy; electronic books; Restaurant management; Business planning -- India